Analysis of Corporate Social Responsibility (CSR) Implementation in The Achievement of Sustainable Development Goals (SDGs): Study of CSR Activities at PT Bio Farma (Persero) West Bandung - Jihan Humaira; Cupian Amir Zaelani (Universitas Negeri Semarang, 2023)
This study aims to analyze and examine the impact of CSR programs that are oriented and support the sustainable development program of PT Bio Farma (Persero). This research also focuses on analyzing the influence of CSR variables on SDGs with ROE as an intervening variable. This type of research is explanatory research with a quantitative approach. The data source comes from secondary data in the form of financial reports and corporate sustainability reports published on the company's official website from 2018 to 2021. The results of this study indicate that PT Bio Farma (Persero) has partially implemented the GRI Standards with a total score of 66%. In addition, the results of data analysis show that: 1) CSR has a significant positive effect on SDGs; 2) CSR has no significant effect on ROE; 3) SDGs has no significant effect on ROE; 4) The effect of CSR through SDGs on ROE is not significant.